A STUDY OF IDIOM TRANSLATION TECHNIQUES AND THEIR EQUIVALENCE IN THE MOVIE JOKER (2019) - Melania Seventina; Srisna J. Lahay (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2026)
This qualitative study aims to find types of idioms as well as describe the techniques used in the subtitle translation of the Joker movie (2019) and their equivalence. The data of this study were analyzed in three steps. First is identifying the type of idiom contained in each data. Second is analyzing what translation techniques are used by the translator. Third is analyzing the equivalence of the translation by comparing the source text and the target text. In the analysis of the data, the researcher used the theory by O'Dell and McCarthy (2017) to classify the idioms, the theory by Molina and Albir (2002) to identify the translation techniques, and the theory by Newmark (1981), as well as Nida and Taber (1974), to determine the equivalence. There are 20 data collected by the researcher. For the types of idioms, there are 17 data representing Fixed Statements, 2 data being Proverbs, and 1 data being Cliche Idiom. Of all the data found, 3 data are using the Reduction technique, 1 data using the Discursive Creation technique, 6 data using the Established Equivalent technique, 3 data using the Linguistic Compression technique, 2 data using the Modulation technique, 2 data using the Transposition technique, 1 data using the Adaptation technique, and 2 data using the Literal Translation technique. As for the translation equivalence, from a total of 20 data, there are 3 unnatural data, and the rest, which means 17 data, have natural translation results.